(untitled) (Bangladesh Journal of Child Health, 2024)
Acute Disseminated Encephalomyelitis (ADEM) is one form of inflammatory demyelinating disorder of central nervous system affecting the children following an idiopathic course of onset and usually monophasic. Recurrent ADEM is a rare entity and will arise a confusion about its diagnosis. There is no definite clinical criteria and treatment protocol for the management of ADEM. Here we report a case of recurrent ADEM where a 6 year old boy presented with recurrent episodes of low grade fever, difficulty in walking, altered sensorium and focal seizure. MRI of brain showed reappearance of demyelinating lesion on the previous site. The gap between first and second episode was six months. After the first attack of ADEM patient were completely recovered both clinically and neuroradiologically with immunotherapy. But after 7 months of disease free remission, patient again developed same features. So we diagnosed the baby as recurrent ADEM based on the consensus criteria of International Pediatric MS study group (IPMSSG). BANGLADESH J CHILD HEALTH 2023; VOL 47 (1) : 51-54